Supraclavicular fasciocutaneous flap for head and neck reconstructive surgery - I. P. Fedzhaha; O. V. Kravets; V. A. Shamrai; V. I. Pivtorak; O. P. Fedzhaha; I. M. Plakhotniuk; A. O. Kovalchuk (Zaporožskij Medicinskij Žurnal)
The purpose of the work is to present modern data on the plastic closure of head and neck defects after malignant tumors removing and in burn injury of this region using supraclavicular flap in the professional literature. This article presents the review and comparison results of modern researches on topographical features of transverse cervical artery and supraclavicular artery, as well as these vessels peak blood flow velocity for the purpose of optimal blood supply preservation in the surgically formed supraclavicular artery flaps. The review describes the study results of topographical features of the cutaneous cervical plexus nerves, consideration of which makes it possible to save or not to save the skin sensibility of flap depending on the surgeon’s goal. The review addresses the analysis results of complications following postoperative defects of soft tissue, skin and mucous membranes surgical closure after head and neck malignant neoplasms removal with a detailed description of the complications nature, localization and size of defects, relation to previous radiotherapy. Our own experience results of reconstruction with supraclavicular flap for head and neck oncosurgery in 77 patients are also presented.